Analysis of key impact factors in new methods implementation in organisations - Gošnik, Dušan (Organizacija (Kranj), 2026)
Background/Purpose: This paper examines the key factors for successful change implementation in organisations, management qualities, and the most common barriers to change implementation. The main change we focus on is implementing new work methods in the organisation, such as Six Sigma, Lean, Lean Six Sigma, Kaizen, and similar methods. Methods: The latest findings from the literature about change management, key success factors and barriers to change implementation are presented. An empirical study of 55 organisations from Slovenia is presented. An online questionnaire was used to gather data. Descriptive statistics were used to analyse the data. The research questions concerned the key factors influencing the successful implementation of organisational changes, the qualities neces- sary for organisational leaders, and the most common barriers to successful implementation. Results: The key factors for successful change implementation are strongly connected to cultural and human-re- lated factors, such as top management and employee involvement. Choosing the right leaders and communicating effectively about the implementation of change are key success factors. Key barriers identified include ineffective means of communication and employee habits and mindsets that do not support change. The most important quality of a manager who is leading organisational change is respect for other parties in the change management process, such as employees. Conclusion: Understanding key success factors and the barriers to implementing change in organisations can im- prove change management practices. The findings contribute to a better understanding of change management in the implementation of new methods in organisations and deliver theoretical and practical implications.
Keywords: change; implementacija; implementation; management; menedžment; method; metoda; sprememba; success; uspeh